A multi-center interventional study to assess pharmacokinetics, effectiveness, and tolerability of prolonged-release tacrolimus after pediatric kidney transplantation: study protocol for a prospective, open-label, randomized, two-phase, two-sequence, single dose, crossover, phase III b trial - Karaterzi, Sinem; Tönshoff, Burkhard; Ahlenstiel-Grunow, Thurid; Baghai, Maral; Beck, Bodo; Büscher, Anja; Eifler, Lisa; Giese, Thomas; Lezius, Susanne; Müller, Carsten; Oh, Jun; Zapf, Antonia; et al. (Frontiers in Nephrology, 2024)
Background: Tacrolimus, is currently the first-line immunosuppressive agent in kidney transplantation. The therapeutic index of tacrolimus is narrow and it has highly variable intra- and inter-individual bioavailability. Non-adherence to immunosuppressants is associated with rejection, which is the main cause of long-term graft loss. Once-daily formulations have been shown to significantly improve adherence compared to twice-daily dosing. Envarsus®, the once-daily prolonged-release formulation of tacrolimus, offers the same therapeutic efficacy as the conventional twice-daily immediate-release tacrolimus formulation (Prograf®) with improved bioavailability, a more consistent pharmacokinetic profile and a reduced peak to trough, which may reduce toxicity. Envarsus® has been approved as an immunosuppressive therapy in adults fbut has not yet been approved in children. The objective of this study is to evaluate the pharmacokinetic profile, efficacy and tolerability of Envarsus® in children and adolescents aged ≥8 and ≤18 years to assess its potential role as an additional option for immunosuppressive therapy. Methods/design: The study is designed as a randomized, prospective crossover trial. Each patient undergoes two treatment sequences: sequence 1 includes 4 weeks of Envarsus® and sequence 2 includes 4 weeks of Prograf®. Patients are randomized to either group A (sequence 1, followed by sequence 2) or group B (sequence 2, followed by sequence 1). The primary objective is to assess equivalency between total exposure (of tacrolimus area under the curve concentration (AUC0-24)) immediate-release tacrolimus (Prograf®) therapy and prolonged-release tacrolimus (Envarsus®) using a daily dose conversion factor of 0.7 for prolonged- versus immediate-release tacrolimus. Secondary objectives are the assessment of pharmacodynamics, pharmacogenetics, adherence, gut microbiome analyses, adverse events, biopsy-proven rejections, difference in estimated glomerular filtration rate (eGFR) and occurrence of donor specific antibodies (DSAs). Discussion: This study will test the hypothesis that once-daily prolonged-release tacrolimus (Envarsus®) is bioequivalent to twice-daily intermediate-release tacrolimus after pediatric kidney transplantation and may reduce toxicity and facilitate medication adherence. This novel concept may optimize the immunosuppressive therapy for more stable graft function and increased graft survival by avoiding T-cell mediated and/or antibody-mediated rejection due to improved adherence. In addition, the study will provide data on the pharmacodynamics and pharmacogenetics of prolonged-release tacrolimus in children and adolescents.